Financial Crisis, Stock Market and Economic Growth: Evidence from ASEAN-5 - Samsi, Siti Muliana; Cheong, Kee Cheok; Yusof, Zarinah (ISEAS - Yusof Ishak Institute, 2019)
This paper examines the effects of the Asian Financial Crisis (AFC) and Global Financial Crisis (GFC) on economic growth in the ASEAN-5 countries. Indonesia, Malaysia and Thailand were found to be most affected by the AFC but not the GFC. Additionally, for Malaysia and Thailand, real output responded positively and significantly to shocks in the stock market. These findings are consistent with the results that show that the shock in the Kuala Lumpur Stock Exchange has a larger effect on real output than other variables for twenty periods. However, a shock in the Bangkok stock exchange has a higher effect on real output and the effect remained strong until the tenth period. This suggests that the stock market is an important economic growth driver in Malaysia and Thailand. © 2019 ISEAS - Yusof Ishak Institute.